The full blood count as a biomarker of outcome and toxicity in ipilimumab‐treated cutaneous metastatic melanoma. (29th September 2016) - Khoja, Leila; Atenafu, Eshetu G.; Templeton, Arnoud; Qye, Ye; Chappell, Mary Anne; Saibil, Sam; Hogg, David; Butler, Marcus O.; Joshua, Anthony M.
Abstract: Ipilimumab produces durable responses in some metastatic melanoma patients. Neutrophil, platelet, and eosinophil to lymphocyte ratios (NLR, PLR, and ELR) may be associated with the immune response in cancer thereby acting as biomarkers of toxicity and efficacy in ipilimumab‐treated patients. Data were collected on clinical characteristics and lactate dehydrogenase (LDH), NLR, PLR, and ELR at baseline, post cycle 2 and at the end of treatment for 183 patients treated with ipilimumab between 2008 and 2015 at the Princess Margaret Cancer Centre. Associations between clinical characteristics, LDH, NLR, PLR, and ELR with toxicity or survival outcomes of progression‐free (PFS) and overall survival (OS) were assessed using univariable and multivariable analysis. Prognostic models of outcome at each time point were determined. Of the 183 patients included, the median age was 58, 85% had M1c disease, 58% were performance status 1, and 64% received ipilimumab as second line therapy. Median follow up was 7.5 months (range: 0.3–49.5), median PFS was 2.8 months (95% confidence intervals (CI): 2.8–3.2), and median OS was 9.6 months (95% CI: 7.9–13.2). Prognostic factors for OS by multivariable analysis were LDH and NLR at all‐time points. Prognostic models using LDH (× 2 upper limit of normal) and NLR 4) differentiated patients into high, moderate, and low risk of death prior to or on ipilimumab treatment ( P  < 0.0001 for each model). No factors were associated with toxicity. Prognostic models based on NLR and LDH values at baseline and on treatment differentiate patients into good, intermediate, and poor prognostic groups and may be relevant in patient management. Abstract : Neutrophil lymphocyte ratios (NLR) is an independent prognostic marker at baseline and during ipilimumab treatment in metastatic melanoma patients.